ANALISIS HASIL PEMBELAJARAN MATEMATIKA SECARA ONLINE SELAMA MASA PANDEMI COVID-19 BAGI SISWA SMK SE KECAMATAN SOSORGADONG - Amril Isman Pasaribu; Mhd Nau Ritonga; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
Abstract This research is background by spreading of corona viruses in the world. In Indonesia, this virus spread in early March 2020. This incident urged the Indonesia government to implement policies in implementing online learning methods. This decision causes learning to be dominated by networks and many students do not have electronic tools in carrying out learning. The purpose of this study is to describe the results of online mathematics learning on students of SMK Negeri 1 Sosorgadong. The approach of the research is descriptive qualitative. Data collection techniques used questionnaires and interviews. The results showed that the results of the questionnaire showed that the results of online mathematics learning were 35.83 (not good category) and the results of the interviews concluded that online mathematics learning was less effective.